The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1161/01.atv.0000236204.37119.8d
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Human Vascular Smooth Muscle Cells From H 2 O 2 -Induced Apoptosis Through Functional Codependence Between HO-1 and AKT

Abstract: Objective-Oxidative stress (OS) induces smooth muscle cell apoptosis in the atherosclerotic plaque, leading to plaque instability and rupture. Heme oxygenase-1 (HO-1) exerts cytoprotective effects in the vessel wall. Recent evidence suggests that PKB/Akt may modulate HO-1 activity. This study examined the role of Akt in mediating the cytoprotective effects of HO-1 in OS-induced apoptosis of human aortic smooth muscle cells (HASMCs). Methods and Results-HASMCs were transduced with retroviral vectors expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 47 publications
2
58
0
Order By: Relevance
“…However, emerging evidence, suggests that HO-1 may also exert cytoprotective effects, independent of heme breakdown [38] by interacting with survival signaling pathways such as PI3K-Akt and p38. We reported recently that HO-1 functions co-dependently with Akt to confer protection from pro-oxidant-induced injury in human aortic smooth muscle cells [25]. Moreover, HO-1 and biliverdin reductase function as phosphoproteins [20,26] and may participate in phosphorylation and activation of PI3K kinase.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, emerging evidence, suggests that HO-1 may also exert cytoprotective effects, independent of heme breakdown [38] by interacting with survival signaling pathways such as PI3K-Akt and p38. We reported recently that HO-1 functions co-dependently with Akt to confer protection from pro-oxidant-induced injury in human aortic smooth muscle cells [25]. Moreover, HO-1 and biliverdin reductase function as phosphoproteins [20,26] and may participate in phosphorylation and activation of PI3K kinase.…”
Section: Discussionmentioning
confidence: 98%
“…HO-1 appears to interact with Akt both at transcriptional [25] the post-translational level [26]. Akt has been reported to induce HO-1 transcriptionally by promoting the activation and nuclear translocation of Nrf2, a key transcription factor involved in regulation of HO-1 gene expression [25,39,40], suggesting that Akt-mediated induction of HO-1 may represent an essential protective response to cellular stress. In addition, Akt phosphorylates HO-1 at serine 188 in vitro and vivo, leading to a modest increase in HO-1 activity [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that HO-1 may have regulated Akt activation via two different mechanisms. Brunt et al have demonstrated functional codependence of HO-1 and Akt in HO-1 treated hydrogen peroxide-induced smooth muscle cell death [46]. Though HO-1 is regulated primarily at the transcriptional level, Akt-induced HO-1 phosphorylation resulted in increased HO-1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic response appears to be mediated by activation of c-jun Nterminal kinase (JNK). Furthermore, in vitro studies have shown that H 2 O 2 can induce apoptosis through a protein kinase C pathway, which is antagonized by Akt and heme oxygenase-1 (Brunt et al 2006). …”
Section: Vascular Cell Apoptosismentioning
confidence: 99%